Pengembangan Kawasan Pariwisata Melalui Branding Desa di Tetebatu Selatan Kecamatan Sikur Kabupaten Lombok Timur - Ahmad Jupri; Nurfadiansih Nurfadiansih; Wahyuni Wahyuni; M. Adi Julva; Eka Sunarwidi P; Tapaul Rozi (Jurnal Gema Ngabdi, 2023)
The tourism sector in the province of West Nusa Tenggara (NTB) is starting to have a major impact on the economy. In fact, the role of tourism in economic growth is quite dominant, when viewed from a number of business sectors in the province of West Nusa Tenggara (NTB). South Tetebatu Village is a Tourism Village which is the Entrance to other Villages in the Southern Region of Mount Rinjani, besides presenting beautiful Accommodations and Landscapes, South Tetebatu Village has interesting characteristics to visit. One of the tourist villages that is currently starting to develop is Tetebatu Selatan Village, Sikur District, East Lombok Regency. This tourist village offers natural beauty that is still beautiful and agro-tourism as a tourist attraction. The various potentials of the village of Tetebatu Selatan can be witnessed directly, but there is still little information disseminated to the wider community, so that these potentials cannot be accessed by the public through social media platforms that are currently developing. The methods used in service activities for branding tourism villages are discussions, observations and demonstrations involving the community, youth and all village officials as well as local and foreign tourists. So that the results obtained from community service activities in Tetebatu Selatan Village can offer and promote a variety of village potentials and uniqueness through leaflets and social media platforms such as Instagram, Facebook, Twitter and Youtube Tetebatu Selatan Village so that they can attract the attention of tourists and the wider community from various regions.